KANDUNGAN LOGAM BERAT PADA JAGUNG YANG DIPUPUK DENGAN KOMPOS IPAL PABRIK PULP DAN KERTAS SERTA KELAYAKANNYA UNTUK KONSUMSI. - Aslim Rasyad; Joko Samiaji; Erwan Efendi (Jurnal Ilmu Lingkungan, 2008)
Sludge as the solid waste produced by pulp and paper industry shows appreciable amounts of essentialelements for plant nutrients, but the use in agriculture is sometime restricted by its heavy metal content. Thisstudy was intended to determine the content of heavy metals in corn plant fertilized by several rates of compostIPAL which was made of sludge obtained from pulp and paper industry. Three levels of compost ie; 10, 20, 30t.ha-1, and NPK fertilizer were applied to corn as well as control in a randomized block design with fourreplications. At around 55 days after planting (DAP), two very young husks (baby corn) and at 90 DAP, 50mature seeds were sampled from each plot. Heavy metals content including Pb, Cd, Cu, and Zn were mesuredfrom these samples by atomic absorbtion spectrophotometer Type NOV-AA 300. It was imperative to note fromthis study that Pb and Cd contents were not detectable both in baby corn and mature corn seed obtained fromplants applied by any level of compost. Copper and Zinc contents were significantly increased in baby corn andmature seed of plants applied by compost compared to that applied by NPK fertilizer or control. However, ifthe heavy metal contents observed from this study were converted to daily tolerable intake for human, thevalues were lower than the maximum tolerable standard, thus both baby corn and mature seed harvested fromcorn fertilized by compost IPAL were save for human consumption.